2014
DOI: 10.1002/micr.22355
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of results obtained with standard and inside out vein graft techniques and their implication on neurotrophin expression in repair of nerve defect: An experimental study

Abstract: Standard vein graft (SVG) and inside out vein graft (IOVG) techniques to promote peripheral nerve regeneration have been widely studied since last two decades. In this experimental study, we attempted to compare these two techniques and analyze the differences in the expression of the neurotrophins during peripheral nerve regeneration. Thirty-six male Wistar rats were used in this sciatic nerve transection model and were divided into two experimental groups (SVG and IOVG) and one sham operated control group. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
4
0
3
Order By: Relevance
“…Ahmed [23] et al compared standard vein grafts with inverted vein grafts for nerve repair, and there was no signi cant difference elicited in the histological, morphometric or muscle mass measurements between groups. Our study also showed that the valves did not induce lumen obstruction in the reversed vein, and regenerating axons could grow from the proximal to the distal end of the vein lumen based on NF200 staining.…”
Section: Discussionmentioning
confidence: 99%
“…Ahmed [23] et al compared standard vein grafts with inverted vein grafts for nerve repair, and there was no signi cant difference elicited in the histological, morphometric or muscle mass measurements between groups. Our study also showed that the valves did not induce lumen obstruction in the reversed vein, and regenerating axons could grow from the proximal to the distal end of the vein lumen based on NF200 staining.…”
Section: Discussionmentioning
confidence: 99%
“…Vein grafts have also been wrapped over epineural repair. There are a few studies informing the superiority of inside‐out vein sleeve technique, however, there are more recent studies informing no difference between the standard and inside‐out vein grafting technique (Ahmed et al, ; Bueno et al, ). It has been reported that vein grafts have neuroregenerative feature.…”
Section: Discussionmentioning
confidence: 99%
“…O tempo de 14 semanas de observação pós-operatória para avaliação histológica do fragmento distal de nervo ciático também se mostra mais adequado. Ahmed et al 98 (2015) relatam que, após 6 semanas, havia poucas fibras nervosas regeneradas no coto distal do nervo ciático em ratos em modelo de 10 mm de lesão e que, após 12 semanas, sua presença era facilmente verificada. Nesse estudo, Ahmed et al 98 usaram uma veia como conduto.…”
Section: Discussionunclassified